Developing database for information system of diagnosing degree of cognitive disorders of patients with discirculatory encephalopathy - Высоцкая, Елена Владимировна; Панферова, Ирина Юрьевна; Рисованая, Любовь Михайловна (Eastern-European Journal of Enterprise Technologies, 2014)
The information system database for determining the degree of cognitive disorders of patients with discirculatory encephalopathy is presented in the paper. It allows storing information about patients, results of clinical and biochemical blood and urine tests, methods and results of testing and surveys. The database is required for ordering the laboratory-diagnostic, clinical-psychopathological and psychognostic information, obtained about a patient. A physical model, based on the relational model was developed. It has a simple and user-friendly data scheme in the form of tables, logically interrelated, and does not disturb the performance and integrity of the database during its modification. This model facilitates the access for medical staff of psychoneurological departments to data for the purpose of timely and correct diagnostics of the degree of cognitive disorders.